A comparative integrated multi-omics analysis identifies CA2 as a novel target for chordoma. Issue 10 (2nd July 2021) - Meng, Tong; Huang, Runzhi; Jin, Jiali; Gao, Jianxuan; Liu, Fuyan; Wei, Ziheng; Xu, Xiaowen; Chang, Zhengyan; Lin, Jun; Ta, Na; Huang, Zongqiang; Yin, Huabin; et al.
Abstract: Background: Chordoma is a rare mesenchymal malignancy, with a high recurrence rate and unclear tumorigenic mechanism. Genetic alterations, epigenetic regulators, and chromatin spatial organization play crucial roles in the initiation and progression of chordoma. In the current study, we aim to uncover the novel therapeutical targets for chordoma via using integrated multi-omics analysis. Methods: The RNA-sequencing (RNA-seq), assay for transposable accessible chromatin by high-throughput sequencing (ATAC-seq), and Hi-C were performed between chordoma and human nucleus pulposus (HNP), along with imageological examination and clinical information. The expressions of identified targets were validated by clinical samples and their functions were further evaluated by cell and animal experiments via gene knockdown and inhibitors. Results: The integrated multi-omics analysis revealed the important roles of bone microenvironment in chordoma tumorigenesis. By comparing the hierarchical structures, CA2 (carbonic anhydrase II) and THNSL2 (threonine synthase-like 2) were identified in the switched compartments, cell-specific boundaries, and loops. Additionally, CA2 was highly expressed in chordoma but barely found in HNP. The cell growth and migration of chordoma cells were dramatically suppressed via inhibition of CA2 either with genetic deletion or pharmaceutical treatment with Dorzolamide HCl. Furthermore, Dorzolamide HCl also regulated the bone microenvironment by blocking the osteoclast differentiation of bone marrow monocytes. Conclusion: This study uncovers the roles of bone microenvironment in the chordoma tumorigenesis and identifies CA2 as a novel therapeutic target for chordoma. Besides, our findings suggest Dorzolamide HCl as a promising therapeutic option for chordoma.